Reading Disability in Indonesian Children’s Literature - Tri Sugiarto (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2020)
The purpose of this article is to examine the representation of disability and to identify the discourse resulted from the pattern of its portrayal in four selected Indonesian children’s shorts stories, namely “Kacamata UFO”, “Gadis Penari”, “Bapak Si Dono”, and “Cerita Rion dengan Sebelah Mata” published in Bobo magazine. Applying the lens of Said’s Orientalism, this content analysis study shows that children with disabilities are presented as weak, dependent, not productive, an object of curiosity and violence, and a vehicle for the growth of other characters in the story. This study concludes that literacy on disability for Indonesian people is significant. Such writing is to provide a positive image and reduce the negative stereotype which is currently shared among society.